Unlocking the potential of minimally processed corn germ oil and high oleic soybean oil to prepare oleogels for bakery application. Issue 12 (13th November 2020) - Zhao, Muxin; Xu, Minwei; Monono, Ewumbua; Rao, Jiajia; Chen, Bingcan
Abstract : Minimally processed plant oil used as a novel source to prepare oleogels for cookie making. Abstract : In this study, the influence of sunflower wax (SFX) concentration (1, 3, 5, 7, and 9 wt%) on the properties of oleogels prepared using expeller-pressed corn germ oil (EPC) or high oleic soybean oil (EPS) was comprehensively investigated. Overall, oleogels can be prepared from both EP oils at an SFX level ≥3 wt%. The strength of oleogels depends on SFX concentration. EPS oleogels had better rheological properties and a higher amount of platelet-like crystals than EPC oleogels. The characteristics of cookies prepared with both oleogels were evaluated and compared to cookies prepared with commercial shortening. The lipid distribution in the cookies as visualized by CLSM suggested that EPS oleogels with a 5 or 7 wt% SFX had a greater possibility of replacing commercial shortening as they exhibited even lipid distribution which enabled good air-incorporation and air retention abilities. This research provides a foundation for developing healthy bakery products by using minimally processed oil based oleogels.